A retomada da ética aristotélico-tomista pela filosofia do direito : o direito natural em destaque - Vieira, Fabrício dos Santos (My University, 2016)
The increasing complexity of intersubjective relations makes the creation and application way to the legal rule develops overcoming the sphere of legality and, as supralegal parameter, highlights the natural law formulation in Aristotle and Thomas Aquinas, for providing very important features to the current situation when dealing with phronesis/prudentia and the mutability of human nature, looking for a thoughtful and adaptable attitude to the situations without neglecting basic timeless principles and practical reasonableness requirements defined by Finnis. In the meantime, the idea of pre-understanding in Gadamer, who says there is a prior understanding working as hermeneutic subjective assumption presiding over all understanding, in case is adapted to the law, appear that, in making the legal decision to the interpretive action as a part of a set concepts and prior knowledge, which somehow sedimented, reaching its conclusions with a minimum of predictability. The thought of Finnis about natural law, based on practical reasonableness and the construction of a philosophical hermeneutics as Gadamer, lead us to believe in the possibility of an ethical foundation for hermeneutics and to the right, without forgetting the contingent and temporary nature of their understanding and application of structures.
A crescente complexidade das relações intersubjetivas faz com que a criação e a forma de aplicação à norma jurídica evoluam superando a esfera da legalidade. Como parâmetro supralegal, destaca-se a formulação do direito natural em Aristóteles e Tomás de Aquino por fornecer características muito importantes para o panorama atual ao tratar da phronesis/prudentia e da mutabilidade da natureza humana. Tal formulação busca uma atitude pensada e adaptável às conjunturas sem descuidar dos princípios básicos atemporais e dos requisitos da razoabilidade prática definidos por Finnis. Nesse ínterim, a ideia de pré-compreensão em Gadamer, que afirma existir uma compreensão prévia funcionando como pressuposto subjetivo hermenêutico presidindo toda a compreensão, caso for adaptada ao direito, constata que, no processo de tomada da decisão jurídica, a ação interpretativa parte de um conjunto de conceitos e conhecimentos prévios, os quais, de certa forma sedimentados, possibilitam alcançar suas conclusões com um mínimo de previsibilidade. O pensamento de Finnis acerca da lei natural, fundada na razoabilidade prática, e a construção de uma hermenêutica filosófica, como a de Gadamer, levam a crer na possibilidade de uma fundamentação ética para a hermenêutica e para o direito, sem olvidar do caráter contingencial e temporal das suas estruturas de compreensão e aplicação.
Keywords: Ética; Direito - Filosofia; Direito natural; Hermenêutica (Direito); Ethics; Philosophy of law; Natural law; Law - Interpretation and construction; Hermeneutics